ANALISIS PERFORMA DAN EVALUASI CAPACITY FACTOR PADA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) 2 MWp SUMALATA GORONTALO - Gabriel Stella Sinay; Mohammad Lanto Kamil Amali; Fuad Pontoiyo; Sarinah Pakpahan (Journal Of Renewable Energy Engineering, 2026)
Solar Power Plants (PLTs) are among the main pillars of Indonesia's renewable energy transition, especially in regions with high solar irradiation potential, such as Gorontalo. This study aims to evaluate the operational performance of the 2 MWp PLTS in Sumalata by calculating the Capacity Factor (CF). The data used includes monthly energy production and solar irradiation during the 2024 operational period. The research method is descriptive-quantitative, calculating the ratio between actual energy output and maximum installed capacity. The results showed that the highest energy production occurred in September at 247,640 kWh, while the lowest was in December at 124,200 kWh. The average Capacity Factor obtained was 15.03%. This value is significantly influenced by weather fluctuations, cloud cover, and solar panel cleanliness (soiling). Although the CF value is within the standard range for PLTS in tropical regions, optimization in preventive maintenance and regular panel cleaning is required to improve system efficiency. This study concludes that the Sumalata PLTS makes a vital contribution to the regional energy mix, but its efficiency remains highly dependent on local meteorological conditions.